Effect of gamma-dose rate on biodegradation of gamma-sterilized biomedical polyolefins - Alariqi, Sameh A. S.; Singh, R. P. (Journal of Polymers and the Environment, 2010)
The aim of the present study is to study the effect of gamma-dose rate on the biodegradation of gamma-sterilized polyolefins. Films of isotactic polypropylene, high density polyethylene and ethylene-propylene (EP) copolymer were sterilized under gamma-radiation with doses of 10 and 25 kGy. Two different (60)Co sources were used with dose rate 600 and 780 Gy h(-1). Neat and sterilized samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and intrinsic viscosity in polymer chains were characterized by FT-IR spectroscopy, SEM and viscometric measurements, respectively. It was observed that both gamma-degradation and biodegradation processes depend on the dose rate of gamma-source. It was found that the biodegradation of gamma-sterilized polyolefins in composting and microbial culture environments increased with decreasing the gamma-dose rate.
Keywords: Biodegradation; Composting and fungal culture; gamma-Dose rate; Polyolefins; Sterilization